Znaczenie terminu mandatum w koncepcji historii zbawienia Filastriusza z Brescii - Szram, Mariusz (Vox Patrum, 2021)
Philastrius, bishop of Brescia (died approx. 387), presented in his treatise Diversarum hereseon liber the concept of history of salvation in three stages: sub mandato, sub lege and sub gratia. The author of the article extracts from the text of Philastrius’ treatise various meanings of the term mandatum, employing historical-comparative and philological methods. Firstly, the term signifies the original commandment given by God to man in Paradise (cf. Gen 2: 16-17). It was sufficient enough to recognize the only Creator and to worship Him properly. However, it was violated by the sin of the first parents, and the Mosaic Law (lex) was its reminder. Secondly, the meaning of the term mandatum comes close to the notion of natural law, although Philastrius does not define it in this way anywhere. He points out, however, that on the basis of a natural ability received from God in the act of creation, man could accept the first commandment. Thirdly, Philastrius used the term mandatum also to describe the commandment of love brought by Christ (gratia Christi). It was the essence of the commandment given to people in the beginning. Thus – in the understanding of Philastrius and this is the originality of his concept – the first commandment, defined by the term mandatum, takes on the character of a peculiar buckle that binds the entire history of mankind: it is both the starting point, established by God, and the arrival point, which is a complement to what was given to man at the beginning and then partially lost.